2019
DOI: 10.1074/jbc.ra119.010084
|View full text |Cite
|
Sign up to set email alerts
|

Heme ligation and redox chemistry in two bacterial thiosulfate dehydrogenase (TsdA) enzymes

Abstract: Thiosulfate dehydrogenases (TsdAs) are bidirectional bacterial di-heme enzymes that catalyze the interconversion of tetrathionate and thiosulfate at measurable rates in both directions. In contrast to our knowledge of TsdA activities, information on the redox properties in the absence of substrates is rather scant. To address this deficit, we combined magnetic CD (MCD) spectroscopy and protein film electrochemistry (PFE) in a study to resolve heme ligation and redox chemistry in two representative TsdAs. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 68 publications
1
34
0
Order By: Relevance
“…For heme proteins, there are essentially three reported cases: myoglobin (10,(19)(20)(21), cytochrome c peroxidase, and horseradish peroxidase (8,9). For a more general approach to study reduction kinetics, a set of six diverse heme proteins was selected; metmyoglobin from horse heart (hhMb), a diheme c protein, thiosulfate dehydrogenase from Allochromatium vinosum (AvTsdA) (22)(23)(24)(25), a B-class dye-decolorizing peroxidase (KpDyP) (26), chlorite dismutases from Nitrospira defluvii (NdCld) (27) and from Cyanothece sp. PCC7425 (CCld) (28), and a coproheme decarboxylase from Listeria monocytogenes (LmChdC) (29).…”
Section: Selection Of Metalloproteinsmentioning
confidence: 99%
“…For heme proteins, there are essentially three reported cases: myoglobin (10,(19)(20)(21), cytochrome c peroxidase, and horseradish peroxidase (8,9). For a more general approach to study reduction kinetics, a set of six diverse heme proteins was selected; metmyoglobin from horse heart (hhMb), a diheme c protein, thiosulfate dehydrogenase from Allochromatium vinosum (AvTsdA) (22)(23)(24)(25), a B-class dye-decolorizing peroxidase (KpDyP) (26), chlorite dismutases from Nitrospira defluvii (NdCld) (27) and from Cyanothece sp. PCC7425 (CCld) (28), and a coproheme decarboxylase from Listeria monocytogenes (LmChdC) (29).…”
Section: Selection Of Metalloproteinsmentioning
confidence: 99%
“…In A. vinosum , the distal axial ligand of the second heme switch from Lys 235 to Met 236 is observed upon reduction of TsdA ( Brito et al, 2015 ). However, an asparagine residue at the Lys 235 equivalent position is highly conserved among proteobacterial thiosulfate dehydrogenases, for example, TsdA from the T. intermedia and S. lithotrophus belonging to Betaproteobacteria , as well as Campylobacter jejuni from Epsilonproteobacteria ( Denkmann et al, 2012 ; Jenner et al, 2019 ). In our results, all Halomonas species and referred M. purpuratum , from the same class as A. vinosum belonging to Gammaproteobacteria , possess TsdA homologues with an Asn residue instead of Lys.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, all Halomonas species and referred M. purpuratum , from the same class as A. vinosum belonging to Gammaproteobacteria , possess TsdA homologues with an Asn residue instead of Lys. As reviewed TsdA containing conserved Asn 235 , the distal axial coordination of the second heme was Met 236 ( Denkmann et al, 2012 ; Brito et al, 2015 ; Jenner et al, 2019 ). Furthermore, it is reported that introducing Lys in place of Asn in the TsdA of C. jejuni , the second heme allows Lys to provide the distal ligand ( Jenner et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7), most of them may not catalyse thiosulfate/sulfur oxidation. The TsdA family proteins are bi‐functional, displaying activity of either thiosulfate dehydrogenase or tetrathionate reductases depending on bacteria species (Denkmann et al ., 2012; Liu et al ., 2013; Jenner et al ., 2019). When TsdA catalyse thiosulfate oxidation, they interact with TsdB.…”
Section: Discussionmentioning
confidence: 99%